Entrepreneurial competence in the field of physical culture and sports: content and essential features - Moldovan, Andriy (ScienceRise: Pedagogical Education, 2020)
The article analyzes scientific approaches of researchers to determination of key notions “entrepreneurship”, “entrepreneurial activity”, “entrepreneurial skill”, “entrepreneurial competence” and tries to specify them, taking into account specific features of the field of physical culture and sport. It is stated, that the level of vocational fitness of future specialists in physical culture is provided by joint presence of comprehensive and special knowledge, abilities, skills, sports and life experience, ability to risk, to overcome difficulties, to find decisions at solving problems, appearing at work of certain complexity in the correspondent specialty. The analysis of educational standards, educational-professional programs and learning-methodical disciplines of the professional training of future specialists in the field of physical culture and sport testifies to insufficient effectiveness of the learning-methodical support of the formation of needed key features of ХХІ century, particularly the entrepreneurial competence development. Entrepreneurship in the field of physical culture and sport, according to the results of the analysis of scientific sources, is presented by the author, from one side, in the social aspect, as a concrete life sphere of society, that covers physical-sanitary, learning-training, competitive and other activity types, from another side – the activity that support them (financing, law, management, development of the material-technical base, communication, research work, training and re-training of staff). From the economic point of view – as a field of non-production sphere, kind of socially helpful work, directed on fiving a special type of services. Thus, a question about training specialists in the field of sport for this type of activity is actualized. Their success directly depends on the entrepreneurial competence development level. So, a conclusion is made that the entrepreneurial competence and entrepreneurial skill of specialists in the field of physical culture and sport provides their success; act as an ability to realize acquired knowledge, abilities and skills, accumulation of the experience in the professional and entrepreneurial activity; an ability to choose means and methods of the entrepreneurial activity, adequate to circumstances of place and time